Temporomandibular joint disorder related to cancer metastasis: A review on reported cases in the literature - Hamed Mortazavi; Anita Taheri; Sara Alehossein; Mehdi Hashemi (Saudi Dental Journal)
Abstract Introduction Metastasis to the temporomandibular joint is an uncommon clinical entity that often mimics benign temporomandibular disorders, leading to diagnostic challenges. This systematic review aimed to consolidate the existing literature on temporomandibular joint metastasis to delineate its clinical and demographic characteristics, diagnostic pitfalls, and treatment approaches. Methods A comprehensive search was conducted across PubMed/MEDLINE, Scopus, and Embase electronic databases. Two independent reviewers screened the titles, abstracts, and full texts of 3,659 articles, ultimately selecting 47 articles encompassing 55 reported cases. Results The analysis revealed a mean patient age of 61.8 ± 13.99 years, with a slight female predominance. Lung and breast cancers were the most common primary sites, with adenocarcinoma being the predominant histopathological type. Clinically, pain, swelling, and restricted mouth opening were the most frequently observed symptoms, although a subset of patients presented with atypical features. Notably, in 49% of cases, TMJ metastasis was detected prior to the diagnosis of the primary malignancy. Multimodal treatment, incorporating combinations of chemotherapy, radiotherapy, and surgery, was the most common therapeutic approach.